Prognostic and Clinicopathological Significance of X-Box-Binding Protein 1 and N-Acetyltransferase 1 in Gallbladder Cancer - Liu, Rushi; Wu, Zhengchun; Zhang, Yuanfang; Miao, Xiongying; Zou, Qiong; Yuan, Yuan; Li, Daiqiang; Yang, Zhulin (Frontiers in Oncology, 2020)
Background: X-box-binding protein 1 (XBP1) and N-acetyltransferase 1 (NAT1) are involved in oncogenesis and progression of many human cancer types. However, the roles of XBP1 and NAT1 in gallbladder cancer (GBC) are never reported. Methods: We examined XBP1 and NAT1 expression in GBC and matched adjacent non-tumor tissues via Western blotting. Then, we assayed XBP1 and NAT1 expression in 215 GBCs, including 69 squamous cell/adenosquamous carcinomas (SC/ASCs) and 146 adenocarcinomas (ACs) with immunohistochemistry. Their prognostic and clinicopathological significance was further evaluated using the χ2 test or Fisher's exact test, Kaplan–Meier univariate survival analysis, and log-rank tests. Results: XBP1 expression was upregulated, and NAT1 expression was downregulated in GBC. Immunohistochemical results showed that XBP1 expression was negatively associated with NAT1 expression in GBC, including SC/ASC and AC. The rate of patients with an age of more than 45 years, positivity of lymph node metastasis, and invasion were significantly higher in SC/ASC than those in AC (all P < 0.05). The percentage of XBP1-positive and NAT1-negative expression was significantly higher in the cases with poor differentiation, advanced tumor, nodes, and metastases (TNM) stage, lymph node metastasis, invasion, and only receiving biopsy in GBC, SC/ASC, and AC (all P < 0.05). XBP1-positive and NAT1-negative expression was positively related to larger tumor size (>3 cm) in GBC and AC. There was a negative association between XBP1 and NAT1 expression in GBC, SC/ASC, and AC (all P < 0.05). Positive XBP1 and negative NAT1 expression was closely associated with decreased overall survival in GBC, SC/ASC, and AC patients (all P < 0.05). The multivariate Cox regression analysis showed that positive XBP1 or negative NAT1 expression was an independent factor for poor prognosis in gallbladder SC/ASC and AC patients. Conclusions: This study indicates that positive XBP1 and negative NAT1 expression are closely associated with the clinicopathological and biological behaviors and poor prognosis in GBC.